Thinking, recording, and writing history in the ancient world - Raaflaub, Kurt A. (John Wiley & Sons Ltd, 2014)
Thinking, Recording, and Writing History in the Ancient World presents a cross-cultural comparison of the ways in which ancient civilizations thought about the past and recorded their own histories. Written by an international group of scholars working in many disciplinesTruly cross-cultural, covering historical thinking and writing in ancient or early cultures across in East, South, and West Asia, the Mediterranean, and the AmericasIncludes historiography shaped by religious perspectives, including Judaism, early Christianity, Islam, and Buddhism.